imlementation of the role playing method to develop socio-emotional development of 5-6 year-old children at NU 76 MUSLIMAT PAUD - ismiyawati (Journal of Education and Teaching Learning, 2026)
This study aims to describe the implementation of the role playing method in developing the social-emotional skills of children aged 5–6 years at PAUD Muslimat NU 76 Baddurih Pademawu Pamekasan. The background of this study is based on the social-emotional problems found in children, such as difficulty cooperating, limited adaptability, emotional instability, and low self-confidence in interacting with peers and their environment. The role playing method was chosen because it is a learning strategy that is appropriate to early childhood characteristics, where children learn through play and direct experience. This research used a qualitative approach with a descriptive research design. Data sources were obtained through observation, interviews, and documentation involving teachers, school principals, and students. Data analysis techniques included data reduction, data presentation, and conclusion drawing, while data validity was tested through source, technique, and time triangulation. The results showed that the implementation of the role playing method helped improve children’s social-emotional skills, including cooperation, communication, empathy, emotional control, and self-confidence. Children became more active, were able to follow rules, understand social roles, and interact positively with peers. Therefore, the role playing method is proven to be an effective, enjoyable, and meaningful learning strategy for developing early childhood social-emotional skills.